HUBUNGAN ANTARA KEPRIBADIAN TAHAN BANTING DENGAN PENERIMAAN DIRI PADA DIFABEL AKIBAT GEMPA YOGYAKARTA - Lestari, Sri Puji (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2013)
Abstract This research aimed to determine the relationship between hardiness personality and self acceptance among Yogyakarta earthquakes survivor who phisically disabled. The hypothesis is a positive relationship between hardiness personality with the disability self acceptance. The Subjects of this research were 60 people. The data collection tools of this research used The Hardiness Personality Scale and The Self Acceptance Scale. Analysis of the statistical method of product moment correlation statistical methods usingSPSS17 for windows. The results of research showed significant positive relationship between personality hardiness with disabilities to self-acceptance r = 0.802 with a chance of error (p) = 0.000 (p <0.01). The research means the proposed hypothesis can be accepted. Personality hardiness contribute to self-acceptance 64.4%, while 35.6% is influenced by other factors not included in this research. Keywords: Personality Hardiness, Self Acceptance